Strengthening of RC beams using bottom and side NSM reinforcement. (15th September 2018) - Sabau, Cristian; Popescu, Cosmin; Sas, Gabriel; Schmidt, Jacob Wittrup; Blanksvärd, Thomas; Täljsten, Björn
Abstract: The allowable strain in fibre reinforced polymers reinforcement is limited by design codes to avoid debonding. The near-surface mounted (NSM) reinforcement technique has been proven to produce better anchorage behaviour compared to externally bonded reinforcement solutions. However, NSM solutions do not always eliminate debonding issues, with concrete cover detachment (CCD) typically occurring in RC beams strengthened for flexure. This experimental study investigated the efficiency of side mounted (S) compared to bottom mounted (B) NSM bars to prevent CCD. The experimental results were compared to models available in the literature that predict the observed failure modes and the crack spacing in the NSM anchorage zone. Compared to B-NSM, the S-NSM solution was successful in avoiding brittle CCD failure and showed increased rotational capacity and energy dissipation at failure. Existing CCD debonding models were found to be conservative.